Developmental regulation of chicken surfactant protein A and its localization in lung. (August 2016) - Zhang, Weidong; Cuperus, Tryntsje; van Dijk, Albert; Skjødt, Karsten; Hansen, Søren; Haagsman, Henk P.; Veldhuizen, Edwin J.A.
Abstract: Surfactant Protein A (SP-A) is a collagenous C-type lectin (collectin) that plays an important role in the early stage of the host immune response. In chicken, SP-A (cSP-A) is expressed as a 26 kDa glycosylated protein in the lung. Using immunohistochemistry, cSP-A protein was detected mainly in the lung lining fluid covering the parabronchial epithelia. Specific cSP-A producing epithelial cells, resembling mammalian type II cells, were identified in the parabronchi. Gene expression of cSP-A markedly increased from embryonic day 14 onwards until the time of hatch, comparable to the SP-A homologue chicken lung lectin, while mannan binding lectin and collectins CL-L1 and CL-K1 only showed slightly changed expression during development. cSP-A protein could be detected as early as ED 18 in lung tissue using Western blotting, and expression increased steadily until day 28 post-hatch. Our observations are a first step towards understanding the role of this protein in vivo . Highlights: Gene expression of chicken SP-A is developmentally regulating peaking at hatch. SP-A is present exclusively in the lung, produced as a glycosylated 26 kDa protein. Protein levels of SP-A significantly increase up to 28 days post hatch. SP-A is found in the extracellular lining fluid of the atria and infundibulum.